ANALISIS PENGARUH PERUBAHAN KEMIRINGAN SUDUT PANCAR ANTENA SEKTORAL TERHADAP KUALITAS LAYANAN JARINGAN SISTEM KOMUNIKASI BERGERAK SELULER - Moch Qadarfi . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2014)
Change the angle of transmit antennas transmit antennas and distance affect the level of signal quality in an area that is covered antennas, because they were planning a change by the tilt angle of the antenna is done to optimize the work of a site. This study analyzes the effect of changes in the tilt angle of the transmit antenna sector for service quality cellular mobile communication system network. The results of the calculation and measurement of the angle changes result in a change of transmit antennas transmit antenna distance calculation results in sector 2 at 2 ° tilt angle (before) condition before changing the tilt angle of the antenna spacing is as far as 2,135 km pancarnya and after conditions change to 4 ° tilt (after) commencing transmit be 2.609 km distance, the calculation in the third sector at a slope angle of 2 ° (before) condition before changing the tilt angle of the antenna spacing is as far as 2,135 km transmit and after changing the tilt angle to be 4 ° (after) transmit be 2.069 km distance and the measurement results distance transmit antenna to the results of the test drive is the best signal results expected in the coverage area of ​​the sector 2 Rasau Jaya on drive test measurement results measurable distance field transmit antenna to tilt 2 ° (before) cover areas as far as 1.12 miles and after changed to 4 ° (after) distance of the transmit antennas as far as 1.44 miles, sector 2 coverage area road Ahmad yani 2 on the measurement results for the tilt 2 ° (before) cover areas as far as 1.26 miles and after changed to 4 ° (after) cover areas as far as 0.98 km, while for the third sector coverage area of ​​Ahmad yani 2 on the measurement results of test drives transmit the measured distance covered as far as 1.07 miles to tilt 2 ° (before) and after changed to 4 ° (after) the distance as far as the transmit antenna 1.12 km, Sector 3 coverage area roads Charcoal unsteady transmit extent measurable distance of 0.94 to 2 ° tilt (before) and as amended on 4 ° tilt (after) transmit distance as far as 0.89 miles, Sector 3 coverage area roads Wonodadi transmit cover areas as far as the distance of 1.30 km at an inclination of 2 ° antenna (before) and after changed widened 4 ° (after) the transmit antenna as far as the distance of 1.20 miles. The results of each change in angle of the transmit antenna is the antenna 3 sectors that cover the area of ​​unsteady Charcoal rx value is -53 dbm level measured on the test drive using tems investigation 8.0.4. The dominant color of the resulting colored dark green with excellent category in the range -68 to 0. Keywords: coverage area, Handoff, Tems investigation 8.0.4, Rx-Level